URGENSI KEBIJAKAN SEKOLAH RAMAH ANAK DALAM PENCEGAHAN KASUS BULLIYING DI TKN 23 DODU - Yuyun Nurul Zannah; Ahmadin; Ade S. Anhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the field of education, there is a growing trend of bullying behavior among early childhood students, which requires systematic intervention through the implementation of child-friendly school policies. TKN 23 Dodu in Bima City is the focus of this study because the school has been striving to implement various preventive strategies to create a safe, supportive, and violence-free learning environment. The objective of this study is to analyze the urgency of child-friendly school policies in preventing bullying incidents and to identify the forms of implementation and their impact on students’ social behavior. This study employs a qualitative approach using a case study design. Data sources include teachers, the school principal, parents, and supporting documents related to the implementation of child-friendly school policies. Data collection methods included direct observation of learning activities, in-depth interviews, and a review of policy documents and children’s behavioral records. Data analysis utilized the Miles and Huberman model, which involves a continuous process of data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of child-friendly schools has a significant impact on fostering a culture of positive interaction, strengthening children’s character, enhancing a sense of safety within the school environment, expediting conflict resolution, and promoting more intensive collaboration between teachers and parents. This policy has proven effective as a preventive strategy in minimizing the risk of bullying among young children, particularly at TKN 23 Dodu in Bima City.